Pancreatic cancer risk in relation to sex, lifestyle factors, and pre-diagnostic anthropometry in the Malmö Diet and Cancer Study. Issue 1 (December 2016) - Andersson, Gustav; Wennersten, Christoffer; Borgquist, Signe; Jirström, Karin
Abstract Background Lifestyle factors may influence the risk of developing pancreatic cancer. Whereas cigarette smoking is an established risk factor, the effects of high alcohol intake and obesity are more uncertain. The aim of the present study was to examine the associations of pre-diagnostic anthropometry, alcohol consumption, and smoking habits with pancreatic cancer risk in a Swedish prospective, population-based cohort, with particular reference to potential sex differences. Methods The studied cohort consists of 28, 098 participants, including all incident cases of pancreatic cancer, in the Malmö Diet and Cancer Study up until December 31, 2013 (n = 163). Non-parametric and chi-squared tests were applied to compare the distribution of risk factors between cases and non-cases. Cox regression proportional hazards models were used to estimate the relationship between investigative factors and pancreatic cancer risk. Anthropometric factors included height, weight, body mass index (BMI), waist and hip circumference, waist-hip ratio (WHR), and body fat percentage. Results BMI was not a significant risk factor for pancreatic cancer, but a higher WHR was significantly associated with an increased risk in the entire cohort (hazard ratio (HR) 2.36, 95% confidence interval (CI) 1.28–4.35, p for trend = 0.009). Regular smoking was a significant risk factor among both women (HR 2.62, 95% CI 1.61–4.27) and men (HR 3.57, 95% CI 1.70–7.47), whereas occasional smoking was a significant risk factor only in women (HR 3.29, 95% CI 1.50–7.19). Passive smoking at work for >20 years was significantly associated with an increased risk in the entire cohort (HR 1.73, 95% CI 1.15–2.58) and in women selectively (HR 2.01, 95% CI 1.21–3.31). Alcohol consumption was not a significant risk factor. A significant interaction was found between female sex and age (p = 0.045), but no other factor, in relation to pancreatic cancer risk. Conclusions WHR was the only pre-diagnostic anthropometric factor associated with pancreatic cancer risk, with no sex-related differences. Regular smoking was confirmed as a significant risk factor in both sexes, whereas occasional and passive smoking were significant risk factors only in women. Despite the lack of a significant interaction between smoking and sex in relation with pancreatic cancer risk, potential sex differences should be considered in future epidemiological studies.